2018
DOI: 10.1016/j.jtcvs.2017.10.141
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter versus surgical valve replacement for a failed pulmonary homograft in the Ross population

Abstract: In Ross patients who require reintervention on the PV homograft, both tPVR and sPVR provide low procedural mortality and comparable midterm outcome with no significant difference in mortality or PV reintervention. However, IE is more common following tPVR. A larger randomized study is needed to determine the role of each procedure in patient management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 29 publications
0
23
1
Order By: Relevance
“…Furthermore, in the current era, homograft failure is increasingly treated percutaneously using transcatheter valves, therefore obviating the need for open reinterventions. [11][12][13] There is wide variability in the reported durability of the Ross operation, and certain early series have reported concerning rates of reintervention. 10 However, proponents of the Ross procedure argue that the risk of reintervention may be largely mitigated by subtle technical refinements based on a thorough understanding of aortic and pulmonary root physiology and mechanisms of valve failure.…”
Section: Favors Mechanical Avrmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in the current era, homograft failure is increasingly treated percutaneously using transcatheter valves, therefore obviating the need for open reinterventions. [11][12][13] There is wide variability in the reported durability of the Ross operation, and certain early series have reported concerning rates of reintervention. 10 However, proponents of the Ross procedure argue that the risk of reintervention may be largely mitigated by subtle technical refinements based on a thorough understanding of aortic and pulmonary root physiology and mechanisms of valve failure.…”
Section: Favors Mechanical Avrmentioning
confidence: 99%
“…9,10 In addition, patients who undergo the Ross procedure are also at risk of late homograft failure, although this problem is increasingly managed using percutaneous approaches in the current era. [11][12][13] Thus, there is equipoise regarding the ideal aortic valve substitute in young and middle-aged adults. Our aim was to compare early and late outcomes in adult patients who undergo the Ross procedure vs mechanical aortic valve replacement.…”
mentioning
confidence: 99%
“…Some of the problems with the literature in this area include lack of uniformity in reporting practices and outcome definitions, heterogeneity in the patient population undergoing TPVR, and an overall small number of cases. The findings of Alassas and colleagues 7 are an important contribution in this area.…”
mentioning
confidence: 77%
“…TPVR endocarditis is a second concern-10.7% in the study by Gillespie and colleagues-and has also been reported by others. 32,33 Alassas and colleagues 34 recently reported on 88 patients undergoing either TPVR (n ¼ 47) or surgical (n ¼ 41) pulmonary valve interventions after a previous Ross procedure. They found a 13% occurrence of endocarditis in the TPVR group and no endocarditis in the surgical group.…”
Section: Pulmonary Allograft Failurementioning
confidence: 99%